CyberKnife and the Future of Cancer Treatment: Interview with Dr Ian Fraser - Janes, Ava (Trinity Student Medical Journal, 2024)
Cancer is a disease that has wedged itself into the mind of society as one of a cruel and devastating nature. As the second leading cause of death worldwide, it comes as no surprise that advances have been made in recent years towards developing potential therapeutic options. However, the most pressing issue today is no longer just the killing of cancer. Instead, the focus lies in extending life while simultaneously avoiding any impairment to that life. As oncologist Dr. Siddhartha Mukherjee so eloquently wrote in this 2010 book, “The Emperor of all Maladies: A Biography of Cancer”, what current therapy truly demands is the use of a “fantastically nimble knife: sharp enough to kill cancer yet selective enough to spare the patient”. It is with this in mind that we can consider the possibility that perhaps this knife exists in CyberKnife. I spoke to Dr Ian Fraser, Consultant Radiation Oncologist at the Hermitage Medical Clinic in Lucan, where he is a member of Ireland’s first and only CyberKnife team, and asked him to offer an introduction to CyberKnife and what he thinks about the future of cancer therapy in Ireland.